Accounting Information System: A Prevailing Tool for Appraising Firm Performance - Teru, Susan Peter; Idoko, Innocent F.; Audu, Philip (International Journal of Accounting & Finance Review, 2018)
The advancement in technology has enabled companies to generate and use accounting information system.  Accounting information system (AIS) is a computer-based application which conveys a new inclination of change from the conservative method of accounting to a computerised method. These advances in information and communication technology (ICT) have reduced the time and cost of transactions by aiding increased and improved transactions and communication for business dealings. It has also improved and advanced the efficiency of businesses by computerising existing operations to improve the performance of their operations. Accounting Information Systems (AIS) can be used by the organizations as a device for achieving a stronger, reliable, and more corporate culture to survive in this competitive environment. Accounting information systems also assist companies to gauge the risk of some operations or predict future warnings using sophisticated statistical software applications. The main objective of this paper is to examine the usage of Accounting Information System for effective decision making and improvedinternal control system on firm performance in which the qualitative data was used reviewing various literatures and other secondary data. This study providesvalue added in accounting literature given the scarcity of works dealing with the relationship between the application and use of AIS and evaluating overall firm performances